Answer:
There are many examples for the first request, but none for the second.
Step-by-step explanation:
a) There is a theorem which states that the sum of two convergent sequences is convergent, so any pair of convergent sequences (xn), (yn) will work (xn=1/n, yn=2/n, xn+yn=3/n. All of these converge to zero)
If you meant (xn) and (yn) to be both divergent, we can still find an example. Take (xn)=(n²) and (yn)=(1/n - n²). Then (xn) diverges to +∞ (n² is not bounded above and it is increasing), (yn) diverges to -∞ (1/n -n² is not bounded below, and this sequence is decreasing), but (xn+yn)=(1/n) converges to zero.
b) This is impossible. Suppose that (xn) converges and (xn+ýn) converges. Then (-xn) converges (scalar multiples of a convvergent sequence are convergent). Now, since sums of convergent sequences are convergent, (xn+yn+(-xn))=(yn) is a convergent sequence. Therefore, (yn) is not divergent and the example does not exist.